A biomechanical model to predict hand-arm vibration when using different vibration damping gloves. (2022) - Sabu, Sooraj; Varun Teja, K.S.R.; Mohan, Sreejith; George, Nivish; Sivapirakasam, S.P.
Abstract: Occupational exposure to the hand-transmitted vibration causes health problems and difficulties in the operators of hand-held power tools. This results in the reduction of manpower and increased costs in terms of compensations remunerated to the affected workers. A principal means to control hand-arm vibration is the use of vibration damping gloves. The primary focus of the current study is to develop biomechanical model of the human bent hand-arm system to predict vibration transmissibility when using different vibration damping gloves. The transmissibility plot was obtained by solving the equations of motion of the biomechanical model considering mass, stiffness and damping coefficient of the gloves. The transmissibility plot obtained from the model indicated that there was no significant reduction in finger vibrations at excitation frequencies less than 100 Hz, even if anti-vibration gloves are used. However, the gloves could appreciably reduce finger vibrations at higher frequencies. The observed response from the model was in agreement with the experimental studies reported in the prior literature suggesting the acceptability of the model for analysing vibration transmissibility characteristics of the human hand-arm system. The model can thus be used to evaluate engineering methods for vibration exposure control during operation of hand-held vibrating tools.